Aging augments obesity-induced thymic involution and peripheral T cell exhaustion altering the “obesity paradox” - Vick, Logan V.; Collins, Craig P.; Khuat, Lam T.; Wang, Ziming; Dunai, Cordelia; Aguilar, Ethan G.; Stoffel, Kevin; Yendamuri, Sai; Smith, Randall; Mukherjee, Sarbajit; Barbi, Joseph; Canter, Robert J.; et al. (Frontiers in Immunology, 2023)
The incidence of obesity, a condition characterized by systemic chronic inflammation, has reached pandemic proportions and is a poor prognostic factor in many pathologic states. However, its role on immune parameters has been diverse and at times contradictory. We have previously demonstrated that obesity can result in what has been called the “obesity paradox” which results in increased T cell exhaustion, but also greater efficacy of immune checkpoint blockade in cancer treatment. The role of obesity, particularly in the context of aging, has not been robustly explored using preclinical models. We therefore evaluated how age impacts the immune environment on T cell development and function using diet-induced obese (DIO) mice. We observed that DIO mice initially displayed greater thymopoiesis but then developed greater thymic involution over time compared to their lean counterparts. Both aging and obesity resulted in increased T cell memory conversion combined with increased expression of T cell exhaustion markers and Treg expansion. This increased T cell immunosuppression with age then resulted in a loss of anti-tumor efficacy by immune checkpoint inhibitor (ICI) in older DIO mice compared to the younger DIO counterparts. These results suggest that both aging and obesity contribute to T cell dysfunction resulting in increased thymic involution combined with increased T cell exhaustion and immunosuppressive parameters which affects immunotherapy efficacy reducing the advantage of obesity in cancer immunotherapy responses.